Magnitude and Pathways of Increased Nitrous Oxide Emissions from Uplands Following Permafrost Thaw - Yang, Guibiao; Peng, Yunfeng; Marushchak, Maija E; Chen, Yongliang; Wang, Guanqin; Li, Fei; Zhang, Dianye; Wang, Jun; Yu, Jianchun; Liu, Li; Qin, Shuqi; Kou, Dan; et al. (Environmental science & technology, 2018)
Permafrost thawing may release nitrous oxide (N2O) due to large N storage in cold environments. However, N2O emissions from permafrost regions have received little attention to date, particularly with respect to the underlying microbial mechanisms. We examined the magnitude of N2O fluxes following upland thermokarst formation along a 20-year thaw sequence within a thermo-erosion gully in a Tibetan swamp meadow. We also determined the importance of environmental factors and the related microbial functional gene abundance. Our results showed that permafrost thawing led to a mass release of N2O in recently collapsed sites (3 years ago), particularly in exposed soil patches, which presented post-thaw emission rates equivalent to those from agricultural and tropical soils. In addition to abiotic factors, soil microorganisms exerted significant effects on the variability in the N2O emissions along the thaw sequence and between vegetated and exposed patches. Overall, our results demonstrate that upland thermokarst formation can lead to enhanced N2O emissions, and that the global warming potential (GWP) of N2O at the thermokarst sites can reach 60% of the GWP of CH4 (vs ∼6% in control sites), highlighting the potentially strong noncarbon (C) feedback to climate warming in permafrost regions.